Pengelolaan Manajemen Kesehatan Keluarga Tidak Efektif Dengan Edukasi Pemberian Air Rebusan Daun Salam Pada Keluarga Dengan Hipertensi: Family Health Management Is Ineffective With Education On Providing Boiled Bay Leaf Water To Families With Hypertension - Chery, Meylina; Muntamah, Ummu (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Hypertension is a chronic disease often referred to as “The Silent Killer” because it can progress without symptoms yet cause serious damage to vital organs. Long-term dependence on pharmacological therapy carries the risk of side effects, highlighting the need for non-pharmacological approaches such as the use of herbal remedies. Bay leaves contain active compounds known to help naturally reduce blood pressure. However, family health management is often ineffective due to limited knowledge and support from family members in managing hypertension. This study aimed to address the problem of ineffective family health management in Mr. S over a period of three days by providing education on the benefits of consuming boiled bay leaf water to help reduce blood pressure. This research employed a qualitative descriptive approach in the form of a case study involving one family with a hypertensive member. Data collection methods included observation, interviews, and documentation. Educational interventions were carried out using health promotion media such as leaflets and flipcharts. The analysis followed the nursing process, including assessment, diagnosis, planning, implementation, and evaluation. Educational efforts directed at Mr. S and his family successfully increased their understanding of hypertension and alternative management strategies. The family demonstrated improved supportive behaviors in managing the health of the affected member, including the use of boiled bay leaf water as a complementary therapy. The patient’s blood pressure showed a decrease during the intervention period. Education on the use of boiled bay leaf water as a non-pharmacological therapy can improve the effectiveness of family health management in hypertensive patients. Family support and involvement play a critical role in the successful management of chronic diseases at the household level.